Penerapan Model Pembelajaran Problem Based Learning Untuk Meminimalisir Kesalahan Belajar Matematika Siswa pada Materi Statistika Kelas XI SMKN 1 Bonepantai - Tiara Trivonia Djikilo; Perry Zakaria; Nancy Katili (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to investigate the application of the Problem-Based Learning (PBL) model in minimising students’ errors in learning mathematics within the statistics curriculum. The research method employed was Classroom Action Research (CAR). The research was conducted at SMKN 1 Bonepantai during the second semester of the 2024/2025 academic year, with a sample of 25 Year 11 students comprising 11 male and 14 female students. Data collection was carried out through observation and tests of students’ mathematical learning errors. The research consisted of two cycles. The results of the study indicate that the application of the Problem-Based Learning (PBL) model can minimise students’ mathematical learning errors in statistics. In Cycle I, the percentage of conceptual errors was 57%, operational errors 73%, and principle errors 61%. Following improvements to the teaching approach in Cycle II, the percentage of student errors decreased to 50% for conceptual errors, 65% for operational errors, and 51% for principle errors. This represents a reduction of 7% in conceptual errors, 8% in operational errors, and 10% in principle errors. Furthermore, the results of observations of teacher and student activities in Cycle II reached 100%, with ratings of ‘good’ and ‘very good’.